تدبر أسلوب التعليل القرآني وأثره على النص = Meditation on Quranic methodology of justification and its impact on the text - Shkokani, Najwa Naief; Elatrash, Radwan Jamal Yousef (Islamic University of Gaza, 2018)
تهدف هذه الدراسة إلى تحقيق التدبر في واحدٍ من الأساليب القرآنية المعجزة وهو أسلوب التعليل، وبيان الغاية من كثرة استخدامه في آي القرآن الكريم وبمواضع خاصةً وبمواضيع غايةً في الأهمية واستنتاج أثرها على المسلم حسب الموضوع المطروح، وبذلك نجد أن منهجاً قد أقام الله  عليه العقائد، والأحكام، والفرائض بالعلل، ومنه نكتسب الطريق الصحيح التفكير، والبناء، وإعمار الأرض، وعلى الرغم من تركيز الخطاب القرآني عليه بكثرة، وتنوع الدراسات حوله قديماً وحديثاً لغوياً وأصولياً؛ إلا أن هناك غيابٌ واضحٌ للدراسات العلمية التي تفرده وتبيِّن أثره وتسهم في إثراء الفكر الإسلامي. ومع الجنوح المادي الكبير في عصرنا هذا، تنشأ مشكلة ضعف التفكير والتعليل والتدبر وهذا له آثاره الوخيمة على المستويين الفردي والجماعي وعلى الأمة ونهوضها وتخلفها، ولا خلاص إلا عند المسلم الذي تتبلور لديه قناعاتٍ فكريةٍ، تدفعه للنهل من المنهج القرآني حول التفكير استمداداً واستهداءاً؛ مما يدفع إلى التعمق في دراسة الأسلوب وأدواته وموضوعه؛ للإفادة منه وعدم الاكتفاء بالتقليد للطرح السابق؛ وقد اعتمدت هذه الدراسة على المنهج الاستقرائي لتتبُّع آيات القرآن الكريم ذات الصلة، للكشف عن المواضيع التي استُخدم فيها أسلوب التعليل، وأهمية ذلك، مع الرجوع إلى تفاسير العلماء في ذلك، ثم اعتماد المنهج التحليلي، واستنتاج التطبيق الصحيح والمنهج السليم في التعامل معها، وأشير هنا إلى أن هذا البحث مستلاً من رسالتي العلمية (أسلوب التعليل في القرآن الكريم وأثره على العالم والمتعلم). ********************************************************* The purpose of this study is to achieve the mastery of one the miraculous methods of the Quran, which is the method of justification. In addition, to indicate the purpose of the frequent of its usage in the Holy Quran, specifically in some special places and important matters. Moreover, to deduce its impact on the Muslim. Therefore, it is observed that the approach that Allah has been used to establish Islamic doctrines, rulings, and obligations is the method of justification. Which the right way of thinking, building, development of the earth, are gained from. Despite the focus of Quranic discourse on it, and various studies were carried out about it in the olden day and nowadays, linguistically and fundamentally, there is still a clear absence of scientific studies that singled out it and its impact and its contribution to the enrichment of Islamic thinking. And with the big physical delinquency in our time, the problem of weakness of thinking, justification and meditation arises, and this has its terrible effects on the individual and the Ummah entirely, as it has effects on its advancement and backwardness, and there is no salvation except in the Muslim who crystallizes his intellectual convictions that will push him to the Qur'anic approach to thinking, and help to study this style, its tools, and its theme in deep, to benefit from it and not merely to imitate the previous proposition. This study adopts the inductive method to trace the relevant verses of the Qur'an that related to the topic, in order to unveil the places which the method justification used, and its importance with reference to the interpretations of the scholars in it. The study also adopts the analytical method, and deduces the correct application and the proper approach in dealing with it. This research is derived from my dissertation titled (The Method of Reasoning in The Quran and its Impact on the Scholar and The Learner).